The Re-shaping of Bodies: A Discourse Analysis of Feminine Athleticism - Aanesen, Sofia M.; Notøy, Runa R. G.; Berg, Henrik (Frontiers in Psychology, 2020)
Slender and skinny body ideals have been associated with psychological disorders such as eating disorders. However, the tendency to promote a “healthier” and more athletic female body ideal has received minimal critical attention. This study aims at exploring the underlying conditions for such an athletic ideal through asking: How is the female athletic body constructed in the pseudonymous contemporary women’s fitness magazine, “Xrzise”? We investigated our object of inquiry through a modified version of Parker’s Foucauldian discourse analysis. We analyzed the interviews of four athletic role models in “Xrzise” and identified four discourses: “Neo-liberal discourse”, “Health discourse”, “Discourse of surveillance and control” and “Discourse of emancipation”. The “ Neoliberal discourse” constructs the female athletic body as something that the individual woman should strive for by appropriately managing her own resources, abilities and skills. The “Health discourse” constructs the female athletic body through a homeostatic logic where the individual is responsible and healthcare experts have the mandate to intervene in order to maintain good health. The “Discourse of surveillance and control” constructs the female athletic body as an internalized panoptic stance, disciplining women to accept hegemonic beauty ideals. The “Discourse of emancipation” accentuates that the female athletic body is alleviated from a culturally rigid body image and instead improved physical performance and functionality are considered good ends. The results and discussion indicate that the female athletic body is a result of a complex nexus of different discourses associated with the powers of economy, sex differences, institutions and ideological forces. We have advocated that magazines like “Xrzise” can have covert disciplinary effects hidden by seemingly well-intentioned motives, which can contribute to women’s objectification of their bodies.